2009
DOI: 10.1073/pnas.0909731106
|View full text |Cite
|
Sign up to set email alerts
|

Activation of nuclear receptor CAR ameliorates diabetes and fatty liver disease

Abstract: Constitutive androstane receptor CAR (NR1I3) has been identified as a central mediator of coordinate responses to xenobiotic and endobiotic stress. Here we use leptin-deficient mice (ob/ob) and ob/ob, CAR ؊/؊ double mutant mice to identify a metabolic role of CAR in type 2 diabetes. Activation of CAR significantly reduces serum glucose levels and improves glucose tolerance and insulin sensitivity. Gene expression analyses and hyperinsulinemic euglycemic clamp results suggest that CAR activation ameliorates hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
247
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 226 publications
(259 citation statements)
references
References 39 publications
11
247
1
Order By: Relevance
“…Hyperglycemia and dyslipidemia are the hallmarks of obesity-associated type 2 diabetes. Activation of CAR by the synthetic agonist TCPOBOP increased insulin sensitivity and ameliorated liver steatosis in both high fat diet (HFD)-and leptin deficiency-induced obesity [77,78] . Several studies have shown that pharmacological activation and the genetic gain-of-function of CAR leads to lower hepatic triglyceride levels, whereas loss of CAR causes basal accumulation of triglycerides in the liver [79] .…”
Section: Car In Energy Metabolismmentioning
confidence: 99%
“…Hyperglycemia and dyslipidemia are the hallmarks of obesity-associated type 2 diabetes. Activation of CAR by the synthetic agonist TCPOBOP increased insulin sensitivity and ameliorated liver steatosis in both high fat diet (HFD)-and leptin deficiency-induced obesity [77,78] . Several studies have shown that pharmacological activation and the genetic gain-of-function of CAR leads to lower hepatic triglyceride levels, whereas loss of CAR causes basal accumulation of triglycerides in the liver [79] .…”
Section: Car In Energy Metabolismmentioning
confidence: 99%
“…8 The liquid diet was ordered from Bio-serv (Frenchtown, NJ, USA), and prepared and maintained as manufacturer's protocols. Because CAR À/À mice are more susceptible to diabetes, 6,7 the maltose in the original recipe was replaced with isocaloric liquid-diet powder. Ethanol concentration was increased gradually from 1 to 5% within 4 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…CAR À/À Mice are More Susceptible to Ethanol-induced Fat Accumulation and Hepatocyte Apoptosis As CAR activation improves metabolism of lipid and glucose in diabetes mellitus, 6,7 we examined whether the CAR À/À mice would exhibit higher grade of steatosis than the wild-type mice by H&E staining and Oil-Red O staining. The long-term ethanol diet feeding caused minor fat accumulation in the wild-type mice (Figures 2a and b).…”
Section: Chronicmentioning
confidence: 99%
See 1 more Smart Citation
“…Some clues have been gathered from targeted gene disruptions in mice that result in a lean phenotype: these include p70 S6 kinase, 21 estrogen-related receptor-a, 22 corepressor RIP140, 23 the liver X receptors (LXRs), 24 CIDEA 25 and, most recently, the constitutive androstane receptor. 26,27 A question yet to be answered is what functions do these molecules share in common that, in their absence, lead to a significant shift in the expression of UCP1 and production of thermogenically active brown adipocytes within typical WAT depots?…”
Section: Targetsmentioning
confidence: 99%